Pemetaan Kompetensi Guru Mata Pelajaran Umum di Madrasah Tsanawiyah - Sumarni Sumarni (Badan Litbang dan Diklat Kementerian Agama RI, 2007)
This research aims at mapping the competencies of general subject matters of the teacher in madrasah (math, English, and Indonesian) including professional competence, individual or personal competence, social competence, and pedagogic competence. the result of this research shows that professional competence and pedagogic competence of general subject teacher in madrasah are still low. the average value for professional competence is 53.4 and average value for pedagogic competence is 53.32. whereas individual competence and social competence of general subject teacher in madrasah mainly are good enough. the average value for individual competence is 83.06% and average value for social competence is 74.47%.